Post-operative neutrophil-to-lymphocyte ratio and outcome after thrombectomy in acute ischemic stroke - Li, Shen-Jie; Cao, Shan-Shan; Huang, Pei-Sheng; Nie, Xin; Fu, Yang; Liu, Jian-Ren (Frontiers in Neurology, 2022)
Background: Neutrophil to lymphocyte ratio (NLR) is a novel inflammatory marker to predict adverse cardiovascular events. However, there is a lack of data on the hemorrhagic transformation (HT) and neurological outcome after mechanical thrombectomy in acute ischemic stroke (AIS). We investigated whether NLR before and after thrombectomy for AIS patients was associated with HT and neurological outcomes. Methods: We performed a retrospective analysis of consecutive patients with anterior circulation AIS who underwent thrombectomy. HT was evaluated by CT within 24 hours after thrombectomy. Clinical data had been collected prospectively; laboratory data were extracted from our electronic hospital information system. NLR were obtained at admission (NLR1) and immediately after thrombectomy (NLR2). The main outcomes were postinterventional intracranial hemorrhage and unfavorable functional status (modified Rankin scale scores of 3-6) three months post-stroke. Results: A total of 258 AIS patients with NIHSS (median 14) were included. NLR2 was higher in patients who developed HT after thrombectomy and unfavorable neurological outcomes three months post-stroke (P<0.001) than in those without HT or favorable outcomes, even after correction for co-factors [Odds Ratio (OR) 1.331 for HT, 95% confidence interval (CI)1.152–1.537, P<0.001, and 1.849 for unfavorable outcome, 95%CI 1.574–2.170, P<0.001]. The optimal cutoff value for the NLR2 as an indicator for auxiliary diagnosis of HT and unfavorable outcome was 8.44 and 8.84 respectively. Conclusions: NLR immediately after thrombectomy is a readily available biomarker of HT and neurological outcomes in AIS patients.